PENGARUH PENGGUNAAN STRATEGI THINK-ALOUD TERHADAP KETERAMPILAN MEMBACA PEMAHAMAN PESERTA DIDIK KELAS V SD NEGERI 106813 AMPLAS - Thara Melanie; Try Wahyu Purnomo; Eva Betty Simanjuntak; Dody Feliks Pandimun Ambarita; Masta Marselina Sembiring (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to determine the effect of using the Think-Aloud strategy on the reading comprehension skills of fifth grade students of Amplas State Elementary School 106813. This study uses quantitative research with a quasi-experimental research method and the research design used is a pretest - posttest control group design. The subjects of this study were 46 students consisting of two classes, each class consisting of 23 students, namely class Vb as the experimental class receiving learning using the Think-Aloud strategy and class Va as the control class using conventional strategies. The instruments used were multiple-choice questions for the pretest and posttest that had been validated. The research instrument tests used were validity tests, reliability tests, difficulty level tests, and different question data tests. The data analysis techniques used were normality testing, homogeneity testing, and an Independent Sample T-Test. The results showed that the average posttest score for the experimental class was 78 with a standard deviation of 7.482, while the score for the control class was 68. The results of the prerequisite analysis test indicated that the data were normally distributed and homogeneous. Based on the results of the Independent Sample T-Test, the calculated t-value was 4.260 with a df of 44 and a 2-tailed significance value of 0.000. Since the 2-tailed significance value of 0.000 <0.05, Ho was rejected and Ha was accepted. Therefore, it can be concluded that there is a significant effect of the use of the Think-Aloud strategy on the reading comprehension skills of fifth-grade students at Amplas Elementary School 106813. The Think-Aloud strategy is effectively used by teachers to improve students' reading comprehension skills.